Dictionary of DNA and genome technology - Singleton, Paul. (Chichester, West Sussex : John Wiley & Sons, 2012)
DNA technology is evolving rapidly, with new methods and a fast-growing vocabulary. This unique dictionary offers current, detailed and accessible information on DNA technology to lecturers, researchers and students throughout the biomedical and related sciences. The third edition is a major update, with over 3000 references from mainstream journals and data from the very latest research - going well beyond the remit of most science dictionaries. It provides clear explanations of terms, techniques, and tests, including commercial systems, with detailed coverage of many important proce.
Dictionary of DNA and Genome Technology; Contents; Preface; Notes for the user; Ready reference; 1-10; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; Q; R; S; T; U; V; W; X; Y; Z; Appendix: Alphabetical list of genera.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Genetic engineering -- Dictionaries; Genomics -- Dictionaries; Genetic Techniques -- English; Genomics -- English; SCIENCE -- Biotechnology; Genetic engineering; Genomics; Gentechnologie; Genetic Techniques; Genomics; Electronic books; Dictionaries; Electronic books; Dictionary